Le cellule staminali: impiego clinico - Vandenbulcke, F.; Beltrame, G.; Vitale, N.D.; Di Matteo, B.; Kon, E. (Lo Scalpello - Journal, 2019)
THE CLINICAL APPLICATION OF MSCS IN ORTHOPAEDICSA systematic review of clinical applications of MSCs in the treatment of knee osteoarthritis (OA). Twenty-threepapers were included in the final analysis (10 on BMAC and 13 on SVF). Of these, only 4 were randomised controlledtrials (RCTs). The Coleman Score, used for bias risk evaluation, revealed an overall poor quality of the studies. Interms of clinical application, despite the apparent safety and the short-term positive clinical outcomes, cliniciansreported different preparation and administration methods. The available literature is not sufficient to make anyrecommendation on the use of either product in clinical practice, even though they have both shown to be safe andhave some short-term beneficial effects.